Hubungan Status Gizi dengan Aktivitas Fisik dan Konsumsi Makanan Manis Kekinian pada Remaja Serta Tinjauannya dalam Pandangan Islam - Aliya Nashwa Faadillah (CV. Green Publisher Indonesia, 2026)
This study explores the relationship between nutritional status, physical activity, and the consumption of contemporary sweet foods among adolescents, while also reviewing this issue from an Islamic perspective. The research aims to examine the impact of these factors on adolescent health, as the growing trend of consuming sweet foods is linked to potential health risks, including obesity and other metabolic disorders. The findings show that there is no significant relationship between sweet food consumption and the nutritional status of adolescents, as measured by the Body Mass Index (BMI). However, factors like the balance of daily physical activity and dietary habits also play crucial roles in determining overall health. The study underscores the importance of maintaining a balanced lifestyle, which is emphasized in Islamic teachings as a way to promote long-term health and well-being.